2022
DOI: 10.1101/2022.05.09.491182
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fin ray branching is defined by TRAP+ osteolytic tubules

Abstract: SUMMARYThe shaping of bone structures relies on various cell types and signalling pathways. Here, we use the zebrafish bifurcating fin rays during regeneration to investigate bone patterning. We found that the regenerating fin rays form via two mineralization fronts that undergo an osteoblast-dependent fusion/stitching until the branchpoint, and that bifurcation is not simply the splitting of one unit into two. We identified tartrate-resistant acid phosphatase-positive (TRAP+) osteolytic tubular structures at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Recent work has shown that lepidotrichia branching process is sensitive to a balance between osteoblast-mediated bone growth and osteolytic tubules expressing ctsk and trap (45). The extent of branching is sensitive to drugs modifying osteoclast behavior and acts as a barometer of osteoclast activity in the development of the zebrafish skeleton.…”
Section: Lrp5 Function Is Necessary To Restrict Resorptive Activitymentioning
confidence: 99%
“…Recent work has shown that lepidotrichia branching process is sensitive to a balance between osteoblast-mediated bone growth and osteolytic tubules expressing ctsk and trap (45). The extent of branching is sensitive to drugs modifying osteoclast behavior and acts as a barometer of osteoclast activity in the development of the zebrafish skeleton.…”
Section: Lrp5 Function Is Necessary To Restrict Resorptive Activitymentioning
confidence: 99%